“AL-MULK (Q.S.67) IN LINGUISTICS PERSPECTIVE: THE PRONOUN STUDY” - Zainuddin IAIN (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: Al-Mulk is a surah in holy Al-Quran within utterances, phrases and even sentences which are created from words and its combinations. Here, the researcher has got attention on words name Pronoun of Arabic to research. The researcher tries to get seven kinds of Pronoun in Al- Mulk, then identify, mean, and describe. Thus, it will be supported by qualitative research method with content analysis. The researcher, finally finds that there are 30 verses in surah Al-Mulk, seven kinds of Pronoun, 14 Dhomier (Arabic Pronoun) and 14 Dhomier Muttashil (Bound Arabic Pronoun), list of Pronoun kinds in Al-Mulk, the number of Pronouns in Al-Mulk, list of words with two bound Pronouns, and list of Pronoun kinds and number of Pronoun in Al-Mulk Keyword: Al-Mulk, dhomier, pronoun, bound,